Artocarpus altilis Extracts as Liquid Electric Mosquito Repellent Against Aedes aegypti (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
ABSTRACT Aedes aegypti is the main vector of dengue virus carriers. One alternative to deal with these problem is by using insecticides derived from the leaves of breadfruit (Artocarous altilis) with the method of liquid electric. The research was purely experimental, with a posttest-only control group design with six variations of extract concentration of 9%, 13%, 20%, 30%, 44%, and 66% with 3 repetitions. The result of Kruskal Wallis test showed that there was a difference of the average number of Aedes aegypti mosquito mortality on various concentration of breadfruit leaf extract, that indicated by significance or probability value of 0.008 <0.05. The deadliest concentration of breadfruit leaf was 66% concentration with mosquito mortality of 83.3% from all mosquito test. The probit analysis obtained LC50 at concentration of 17.850% and LC90 at concentration of 98.348%. Keywords: Aedes aegypti, Breadfruit Leaf Extract, Liquid Electric ABSTRAK Aedes aegypti merupakan nyamuk yang menjadi vektor utama pembawa virus dengue. Salah satu alternatif lain untuk menangani permasalahan tersebut yaitu dengan menggunakan insektisida yang berasal dari tumbuhan atau nabati, yaitu daun sukun (Artocarous altilis) dengan metode elektrik cair. Jenis penelitian ini adalah eksperimen murni, dengan rancangan posttest only control group design dengan enam variasi konsentrasi ekstrak sebesar 9%, 13%, 20%, 30%, 44%, dan 66% dengan masing-masing 3 kali pengulangan. Hasil uji Kruskal Wallis menunjukkan bahwa ada perbedaan rata-rata jumlah kematian nyamuk Aedes aegypti pada berbagai konsentrasi ekstrak daun sukun, ditunjukkan dengan nilai signifikansi atau probabilitas adalah 0,008 < 0,05. Konsentrasi ekstrak daun sukun yang paling banyak mematikan nyamuk yaitu konsentrasi 66% dengan kematian nyamuk 83,3 % dari keseluruhan nyamuk. Uji analisis probit didapatkan LC50 pada konsentrasi 17.850% dan LC90 pada konsentrasi 98.348%. Kata kunci: Aedes aegypti, Ekstrak Daun Sukun, Elektrik Cair